Association between physical activity dimensions and the risk of hypertension among middle and older adults: A cross-sectional study in China - Zhou, Linlin; Feng, Wei; Xiang, Na; Cheng, Yue; Ya, Xudong; Wang, Mingxia; Wang, Xingqi; Liu, Yujia (Frontiers in Public Health, 2022)
Background It is known that insufficient physical activity is associated with the risk of hypertension, but the relationship to different physical activity dimensions within hypertension risk remains to be elucidated. Objective The objective of this study is to identify the association between physical activity intensity, frequency, duration, and volume with hypertension risk. Meanwhile, a dose-response experiment is conducted to determine the relationship between physical activity level and hypertension risk. Methods Data came from the 2018 China Health and Retirement Longitudinal Study (CHARLS, 2018), which included 14266 participants over the age of 45. Binary logistic regression models were established to assess the associations between different dimensions of physical activity and the risk of hypertension. Restricted cubic spline analysis was used to examine possible non-linear associations between physical activity volume and hypertension risk. Results For frequency, lower hypertension risk was associated with performing vigorous physical activity 6–7d/w (OR 0.82, 95%CI 0.73–0.93) and moderate physical activity 6–7d/w (OR 0.89, 95%CI 0.80–0.99). No significant association between any light physical activity frequency and hypertension was observed before and after being adjusted. For the duration, lower hypertension risk was observed in performing vigorous physical activity ≥240 min/d (OR 0.85, 95%CI 0.75–0.97) and moderate physical activity ≥240 min/d (OR 0.83, 95%CI 0.71–0.97). For volume, the risks of hypertension in the participants who reported TPA in the 3th and 4th of quantiles were reduced by 18% (OR 0.82, 95%CI 0.72–0.95) and 22% (OR 0.78, 95%CI 0.68–0.91). A non-linear dose-response association between total physical activity and the risk of hypertension was shown among all of the participants (P non-linearity < 0.05). Conclusion Higher frequency and longer duration of vigorous physical activity or moderate physical activity were significantly associated with a lower risk of hypertension. Higher physical activity levels were associated with a lower risk of hypertension and there was an inverse non-linear dose-response relationship between weekly total physical activity and the risk of hypertension. These findings provide further proof that hypertension could be prevented through increased physical activity.